Performance Management of State Civil Apparatus in the Staffing and Human Resource Development Agency of East Bolaang Mongondow Regency - Lengkong, Siedmy Chyril; Bogar, Wilson; Wawointana, Thelma; Mandagi, Marthinus (Technium Social Sciences Journal, 2025)
This study aims to determine and analyze the State Civil Apparatus (ASN) Performance Management of the Personnel and Human Resources Development Agency in East Bolaang Mongondow Regency which includes the stages of performance planning, stages of implementation, monitoring, and performance coaching, stages of performance evaluation, and stages of follow-up on performance evaluation results. This research used descriptive qualitative methods. The research instruments used were interview guides, documents/literature, and photos/documentation. Data collection techniques were carried out through interviews, observation, and documentation. Based on the results of the research, the State Civil Apparatus (ASN) Performance Management at the Staffing and Human Resources Development Agency of East Bolaang Mongondow Regency has not been carried out optimally due to the lack of understanding of appraisal officials and assessed employees regarding the State Civil Apparatus (ASN) Performance Management. The recommendation of this research is for the Personnel and Human Resources Development Agency of East Bolaang Mongondow Regency to carry out socialization and training on performance management of the State Civil Apparatus so that every State Civil Apparatus in the Personnel and Human Resources Development Agency of East Bolaang Mongondow Regency knows how to implement performance management in accordance with the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 6 of 2022 concerning Performance Management of State Civil Apparatus Employees.